ChemInform Abstract: YCu(TeO3)2(NO3) (H2O)3: A Novel Layered Tellurite. Issue 43 (7th October 2016) - Mills, Stuart J.; Dunstan, Maja A.; Christy, Andrew G.
Abstract: Dark blue prisms of the title tellurite are prepared by hydrothermal treatment of a 1:1:1 molar mixture of Y(NO3 )3, Cu(NO3 )2, and Te in H2 O (autoclave, 473 K, 3 d).